Potensi Wisata Moslem Friendly di Desa Wisata Taro Tegallalang Gianyar Bali - Wirawan, Putu Eka (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
This study aims to analyze the potential for developing halal tourism-based tourism in the Taro Tegallalang Gianyar Tourism Village, Bali. This study used a qualitative research method with a descriptive approach, because most of the data was obtained by interviewing stakeholders and tourists visiting the research location. The results of this study are as follows: the potential for developing halal tourism is very open, because the availability of friendly food and beverage accommodation for Muslim tourists is quite a lot; there is a skewed stigma in the community regarding halal tourism, it needs socialization to the community; and the need to make regional regulations that refer to central government regulations. The conclusion from this study is that most of the tourist attractions in Bali are open to adapting changes that do not conflict with local culture, so that the Taro Tourism Village also has the potential to be developed as a halal or Muslim friendly tourist attraction. This study also suggests that several tourist attractions in Bali are open to changes as long as they do not conflict with local beliefs and wisdom, so that the potential for a large tourism market from Muslims in the world can be utilized for the sustainability of Bali tourism. Keywords: Tourism potential, Moslem friendly, Taro Bali Tourism Village